Medication adherence and its associations with socio-demographic factors and clinical profiles among type 2 diabetes mellitus patients - Abdullah, Nor Fadhilah; Lee, Khuan; Cheong, Ai Theng; Sowtali, Siti Noorkhairina (2018)
Diabetes mellitus is a chronic non-communicable disease and is increasing in trend due to modernization and unhealthy lifestyle. Antidiabetic medication is one of the pharmacological approach being prescribed to the diabetes patients for optimizing the blood glucose level. However, non-adherence towards medication was identified as one of the barrier to the effectiveness of diabetes management. The aim of this study is to determine the adherence rate among type 2 diabetes patients towards their anti-diabetic medications and its association with socio-demographic and clinical profiles. A cross sectional descriptive study was conducted on 427 randomly selected diabetes patients who had attended two public hospitals implementing Total Hospital Information System (THIS) in Malaysia. Data collection was performed using validated Medication Compliance Questionnaire (MCQ). Data obtained were analyzed using SPSS software version 22. A multivariable logistic regression analysis was used to examine the association between patients’ profile and medication adherence. The confidence interval was set at 95% CI with p value of 0.05. Overall, a response rate for this study was 93.4%. The adherence rate of the diabetes patients was 53.4% with the Indian and Chinese ethnics were more likely to adhere towards their medication prescription with p=0.017 and p=0.046 respectively. There was also a significant association between HbA1c level with patients’ medication adherence (p=0.001). As a conclusion, the contributing factors other than socio-demographic and clinical profile were suggested to be explored subjectively from patients’ point of view to facilitate a formulation of patient-centred strategies on adherence to antidiabetic medication.